Investigating the Impact of Formative Years in Developing Social Change Leaders: A Study Using Hermeneutic Phenomenology - Ogutu, Moses Onyango (Graduate School of Business (GSB), 2023)
Social change leaders address systemic inequities, aiming to create a just society through transformation. The existence of social change leaders has resulted in studies or models exploring social change leadership, including motivators or values that characterize leaders, such as common citizenship and concern for humanity. This study investigates the impact of formative years in developing social change leaders and the area of interest of social change leaders. Using hermeneutic phenomenology and qualitative interviews with social change leaders, the study found that formative years contribute to the development of social change leaders in two ways. First, one of the critical dimensions of formative years, socio-economic background growing up grounds social change leaders' understanding of their community, gradually changes their perception of and approach to leadership and teaches the principles of social change leadership (interconnection between individual values, group values, and societal values). Second, formative years influence the area of interest, or the social challenge addressed. The study also found that social change leaders address challenges they have faced, feel a sense of responsibility, and have a deep interest in the challenges they address. The findings suggest that: to understand social change leaders and their interest in social change work, we need to understand the existence of the challenges they are working to address and their lived experience with such challenges. Equally, to solve the systemic, endemic, and emerging social challenges, focus should be on developing leadership qualities in young adults or working with individuals and communities to address challenges facing them.